A Ku-Band Dual Linear-Polarized 2×4 Microstrip Patch Subarray with a Rhombic Feed Transmission Line for Enhanced Cross-Polarization Cancellation - Yanti, Riyani Jana; Wahdiyat, Aditya Inzani; Jusoh, Muzammil; Apriono, Catur (Engineering, Technology & Applied Science Research, 2026)
Α Ku-band, dual-linear polarized, 2×4 microstrip circular patch subarray antenna with co-aligned elements and a rhombic feed transmission line to is proposed to improve cross-polarization performance, enhance link reliability, and provide a compact, single-port solution for mobile satellite terminals. This design directly addresses key limitations of existing mobile satellite antennas, including polarization mismatch and degraded performance under dynamic operating conditions. Mobile satellite systems on moving platforms, such as vehicles and emergency terminals, have difficulty maintaining polarization isolation and stable performance due to motion and varying environmental conditions. The proposed antenna is optimized for communication satellite systems, integrating with Satellite Nusantara Satu. The simulation results demonstrate good impedance matching, with an S11 of –47.43 dB at 12.55 GHz, a 659 MHz bandwidth, and a 9.28 dBi gain. However, the measured results indicate a slight frequency shift to 12.32 GHz, with an S11 of –20.51 dB, a bandwidth of 364 MHz, and a gain of 8.77 dBi, due to variations in fabrication tolerance and substrate permittivity. The subarray achieves a high Cross-Polarization Level (CPL) of more than –45 dB, confirming that the antenna is reliable for Ku-band satellite communication and provides enhanced polarization purity under continuous motion and varying environmental conditions, including vibration, temperature fluctuations, humidity, and physical obstructions.